Clinical outcomes and safety comparison of gemcitabine plus cisplatin, capecitabine monotherapy, and gemcitabine plus oxaliplatin in the management of gallbladder carcinoma: a comprehensive meta-analysis - Rahman, Sanjida (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2024.